Triticale: agroecological and economic value, ongoing state at the cases of Eurasian, North- and South American and Australian areas - C. І. Тарасюк (Plant Varieties Studying and Protection)
State and prospects of growing for Triticale crop at the territory of leading states of the world are highlighted across space and time. Observing the trend of changes in planting acreage and the product yield of wheat and rye hybrids, their popularity in agrarian and industrial fields of a whole range of countries in Asia, Northern and Southern America, Australia, a Ukrainian manufacturer is invited to consider and reasonably assess this crop and thus list in the composition of planted acreage the national nowadays varieties of triticale as an essential or strategic system component.